Penggunaan Media Sosial Sebagai Upaya Pemberdayaan Usaha Mikro Kecil dan Menengah - Andre Dwiparma; R. Hamdani Harahap; Heri Kusmanto (Universitas Medan Area, 2022)
The purpose of this study is to examine the empowerment of Micro, Small and Medium Enterprises (MSMEs) which is one of the driving forces of Indonesia's economic growth, especially in the Workshop Market, Perbaungan District, Serdang Bedagai Regency. This is because MSMEs can create the most employment opportunities so that they are able to make a major contribution to employment. The type of research used in this research is qualitative research with descriptive analysis approach. Primary data collection techniques are observation and interviews, and secondary data collection techniques are carried out by means of library research, and documentation. The results of the study state that social media platforms play an important role in marketing MSME products at the Workshop Market during the COVID-19 pandemic. The trial of optimizing the use of social media as a good product marketing tool for MSME actors in the Workshop Market can increase sales of MSME products, and reach consumers on a scale throughout Serdang Bedagai Regency and outside the Serdang Bedagai Regency area. Utilization of social media as an effective supporting tool for MSMEs to run during the COVID-19 pandemic because MSME actors in the Workshop Market can still carry out their business activities while still complying with and implementing health protocols.